2016
DOI: 10.18632/oncotarget.9498
|View full text |Cite
|
Sign up to set email alerts
|

Increased translocation of antigens to endosomes and TLR4 mediated endosomal recruitment of TAP contribute to nicotine augmented cross-presentation

Abstract: Cross-presentation by dendritic cells (DCs) requires surface molecules such as lectin, CD40, langerin, heat shock protein, mannose receptor, mediated endocytosis, the endosomal translocation of internalized antigen, and the relocation of transporter associated with antigen processing (TAP). Although the activation of α7 nicotinic acetylcholine receptor (α7 nAchR) up-regulate surface molecule expression, augment endocytosis, and enhance cross-presentation, the molecular mechanism of α7 nAchR activation-increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…Our previous study showed that TLR4-MyD88-IRAK4-dependent TAP translocation from endoplasmic reticulum toward endosomes facilitates DC cross-presentation [ 18 ]. Other reports also demonstrated that the endosomal recruitment of Sec61, which depends on NF- κ B activation, is responsible for cross-presentation [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study showed that TLR4-MyD88-IRAK4-dependent TAP translocation from endoplasmic reticulum toward endosomes facilitates DC cross-presentation [ 18 ]. Other reports also demonstrated that the endosomal recruitment of Sec61, which depends on NF- κ B activation, is responsible for cross-presentation [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…TLR4, as an essential signal pathway of pattern recognition receptor, could be internalized by LPS-stimulated cells and promote myddosome formation, which facilitate the endosomal recruitments of TAP and Sec61 [ 15 , 18 , 20 , 21 ]. As PYR-41 and thalidomide inhibited the endosomal recruitments of p97/Sec61 (Figures 5 – 7 ) and attenuated NF- κ B activation ( Figure 8 ), we wonder whether PYR-41- impaired cross-presentation and thalidomide-impaired cross-presentation were due to the inhibition of myddosome formation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations